Factors Affecting the Continuous Use of Cloud Computing Services from Expert's Perspective - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah; Abu-Shanab, Emad A. (IEEE, 2017)
This research aims at validating the vital factors that affecting the continuous use of cloud computing services through literature review and experts’ evaluation. These factors are factors that have an effect on the decision makers to forge ahead in the use of cloud computing services in their various organizations. Semi-structured interviews using email were carried out with twenty-three experts (nine IT practitioners and fourteen academics) in order to realize the identified objective. Based on the expert’s perspectives, the followings factors; cost reduction, top manager’s support, relative advantage, compatibility, perceived trust, complexity competitive pressure, perceived security and privacy, IT readiness and government support have the greatest ten are the ten noteworthy factors which have effect on the decision makers to further the use of cloud computing services. The findings of this study will be the building block in developing a conceptual model for the continuous intention to use of cloud computing services in small and medium enterprises (SMEs) in Malaysia.